WORK OF SOCIAL PEDAGOGUE IN SCHOOL ENVIRONMENT TO DEVELOP SOCIAL SKILLS OF TEANAGERS - Kraģe, Indra (Education Reform: Education Content Research and Implementation Problems, 2019)
In the research “Work of social pedagogue in school environment to develop social skills of teenagers”, the author focuses on the need for the development of teenagers' social skills in the modern era of digitalization and information technology. Social skills of teenagers today are underdeveloped. The aim of the thesis is to explore different authors’ research on teenagers’ biopsychosocial development – physical development, the nature and the social psyche, and analyse socialization of teenagers in the school environment. Theoretical and practical methods such as team work, group work and social pedagogical observation are used. Teamwork model and a programme for development of teenagers’ social skills has been described.